Respuesta :
Answer:
[tex] y(t) = 2e^t -e^{-t} [/tex]
Step-by-step explanation:
Assuming this complete problem: "In this problem,
y = c1ex + c2e−x
is a two-parameter family of solutions of the second-order DE
y'' − y = 0.
Find a solution of the second-order IVP consisting of this differential equation and the given initial conditions.
y(0) = 1, y'(0)= 3"
Solution to the problem
For this case we have a homogenous, linear differential equation with order 2, and with the general form:
[tex] ay'' +by' +cy=0[/tex]
Where [tex] a =1, b=0, c=-1[/tex]
And we can rewrite the differential equation in terms [tex] y = e^{rt}[/tex] like this:
[tex] [e^{rt}]'' -e^{rt}=0[/tex]
And applying the second derivate we got:
[tex] r^2 e^{rt} -e^{rt}=0[/tex]
We can take common factor [tex] e^{rt}[/tex] and we got:
[tex] e^{rt} (r^2-1) =0[/tex]
And for this case the two only possibel solutions are [tex] r=1, r=-1[/tex]
And the general solution for this case is given by:
[tex] y = c_1 e^{r_1 t} + c_2 e^{r_2 t}[/tex]
Replacing the roots that we found we got:
[tex] y = c_1 e^{t} +c_2 e^{-t}[/tex]
Now we can find the derivates for this last espression
[tex] y' = c_1 e^t -c_2 e^{-t}[/tex]
[tex] y'' = c_1 e^t +c_2 e^{-t}[/tex]
From the initial conditions we have this:
[tex] y(0)=1 =c_1 e^{0} +c_2 e^{-0}= c_1 +c_2[/tex] (1)
[tex] y'(0) =3= c_1 e^{0} -c_2e^{-0}= c_1 -c_2[/tex] (2)
If we add equations (1) and (2) we got:
[tex] 4 = 2c_1 , c_1 = 2 [/tex]
And solving for [tex]c_2[/tex] we got:
[tex] c_2=3-c_1= 3-2 = 1[/tex]
So then our general solution is given by:
[tex] y(t) = 2e^t -e^{-t} [/tex]